Nível, potencial para mudança e preferências de atividade física em discentes da área da saúde da Universidade Federal do Maranhão - OLIVEIRA, Elaynne Silva de (2018)
The objective of the study was to evaluate the number of individuals and physical and associated factors in the university population of the Center of Biological Sciences and Health - CCBS of the Federal University of Maranhão, Bacanga campus, through an online questionnaire. This is a longitudinal prospective study, carried out with 284 discourses regularly enrolled in the 9 undergraduate courses of the Center for Biological and Health Sciences - CCBS, UFMA. For data collection, use an online questionnaire (MAFIS) with 41 questions. The data were analyzed in the statistical program SPSS, version 23.0, by means of descriptive statistics in the form of absolute frequency and percentage, to verify the NAF and associated factors. The chi-square test was used with later assembly of logistic regression model, the significance level was 5%. It was observed a high prevalence of physical inactivity in leisure (NAFLAZ) among university students, more than 50% of the sample was classified as inactive or insufficiently active, the majority of the participants are female students, 61.3% 40.8% do not practice physical activity (AF), but 91.5% think about doing or doing more AF, 72.5% like to do and 47.5% have practice as a priority. Sex, AFLAZ as a priority, like to do AFLAZ, daily time for study and sitting time, AFLAZ compared to last six months, priority AF, wake up an hour earlier to do AFLAZ, learn a new AF, do not lose patience in situations of daily life and AF during the last six months) had an association with NAFLAZ. college students who responded to more AF compared to the last six months were 27 times more likely to remain active compared to people who did less AF in the last six months, people who responded to like AFLAZ increased their chances of being active 12 times longer , those who consider AFLAZ a priority had their chance increased by 1.2 times, since people who prioritize competitive AF have 4x more chances to make AF compared to those who do not prioritize a specific type of AF, those who consider themselves "quite capable" of waking up 1 hour earlier to do AF, have increased their chances of being physically active by more than 4 times. The data show that they should be a concern regarding the prevalence of physical disability among the students of the health area. The results of this study were ancillary in the planning of strategies and actions aimed at the implementation of programs and reports that encourage the creation of spaces and the options for the practice of activities within the university.